2x+7(3x-4)=-2-3x

Simple and best practice solution for 2x+7(3x-4)=-2-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+7(3x-4)=-2-3x equation:


Simplifying
2x + 7(3x + -4) = -2 + -3x

Reorder the terms:
2x + 7(-4 + 3x) = -2 + -3x
2x + (-4 * 7 + 3x * 7) = -2 + -3x
2x + (-28 + 21x) = -2 + -3x

Reorder the terms:
-28 + 2x + 21x = -2 + -3x

Combine like terms: 2x + 21x = 23x
-28 + 23x = -2 + -3x

Solving
-28 + 23x = -2 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-28 + 23x + 3x = -2 + -3x + 3x

Combine like terms: 23x + 3x = 26x
-28 + 26x = -2 + -3x + 3x

Combine like terms: -3x + 3x = 0
-28 + 26x = -2 + 0
-28 + 26x = -2

Add '28' to each side of the equation.
-28 + 28 + 26x = -2 + 28

Combine like terms: -28 + 28 = 0
0 + 26x = -2 + 28
26x = -2 + 28

Combine like terms: -2 + 28 = 26
26x = 26

Divide each side by '26'.
x = 1

Simplifying
x = 1

See similar equations:

| -8x^2+24x-18= | | -16+x=450 | | 5x^2+50x=0 | | -5x+x=-16 | | 120x^2-272x+120=0 | | 5*5*5*5= | | 2t^2+2t=3 | | 10-3(-8-2)= | | 120x^2-272x+102=0 | | 10x-0.375-4x=6x | | 2+x=16-6x | | 30a=2a-8 | | 976x-x^2=213.495 | | 1/14=27/7*1/30 | | 10x-2y=5 | | -2x^2+17x-8=0 | | 6x-2y=1 | | -99=33y | | 8j-4k=4 | | 5(k-2)-6=5k-(4k-3) | | 3j+4k=23.5 | | 11f+10g=25 | | Y=150x+800 | | 22=-2+3s | | -2-19= | | 4m(4n-8)+6mn-2m= | | -39(11x)+26(24x)= | | 3r-6t=15 | | 6r-6t=6 | | 4x=14-2x | | 6=3n-5 | | 2n+6=5n-5 |

Equations solver categories